Crossing experiment of Anopheles maculatus form K and Anopheles willmori (James) (Diptera: Culicidae) - Pradya Somboon (2018)
We recently reported crossing experiments between Anopheles maculatus form K and five members of the Maculatus group to support the specific status of form K. In the present study, we performed further crosses between form K and a sixth species of the Maculatus group, Anopheles willmori (James). Low viability was observed in hybrid males and females. All hybrid males were sterile with atrophied testes, or partially sterile with abnormal spermatozoa. The hybrid females showed normal ovaries. The ovarian nurse cell polytene chromosomes of the F1hybrid females displayed complete asynapsis. Backcrossing showed low viability. All males were sterile with atrophied testes or partially sterile with abnormal spermatozoa, and the females showed varying degrees of atrophied ovaries. The results provide clear evidence that form K is not conspecific to A. willmori supporting previous studies that form K represents another species of the Maculatus group. © 2008 Springer-Verlag.